2022
DOI: 10.3389/fvets.2022.975113
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and minimal inhibitory concentrations of ceftiofur in tear film following extended-release parenteral administration (Excede®) in dogs

Abstract: PurposeDescribe the pharmacokinetics of extended-release parenteral ceftiofur (Excede®) in canine tear film and compare these concentrations to minimal inhibitory concentrations (MICs) of ceftiofur against common ocular pathogens in dogs.MethodSix dogs of various breeds were enrolled. Disruption of blood-tear barrier was achieved with histamine-induced conjunctivitis to ensure clinical relevance of the results. Each dog received a single subcutaneous injection of 5 mg/kg Excede®, followed by tear collection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Indeed, canine eyes with various pathologies requiring topical NSAIDs (eg, conjunctivitis, uveitis, cataracts) are known to have "leaky" conjunctiva, that is, a breakdown of the blood-tear barrier that might allow tear film compounds to reach the systemic circulation at higher levels and vice versa. 25,[32][33][34][35] Finally, the small sample size must be taken into consideration when interpreting the statistical relationship found between endoscopic scores and plasma ketorolac concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, canine eyes with various pathologies requiring topical NSAIDs (eg, conjunctivitis, uveitis, cataracts) are known to have "leaky" conjunctiva, that is, a breakdown of the blood-tear barrier that might allow tear film compounds to reach the systemic circulation at higher levels and vice versa. 25,[32][33][34][35] Finally, the small sample size must be taken into consideration when interpreting the statistical relationship found between endoscopic scores and plasma ketorolac concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…While systemic antimicrobials have been detected in the tear film following systemic administration, 68,69 Collins et al 70 . and Bowden et al 71 . concluded that the achieved concentrations of doxycycline and ceftiofur, respectively, in the canine tear film were too low for any effective antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,23,24 We show treating infected corneal ulcers with a systemic antimicrobial had no effect on whether an infected ulcer tested positive or not. While systemic antimicrobials have been detected in the tear film following systemic administration, 68,69 Collins et al 70 and Bowden et al 71 concluded that the achieved concentrations of doxycycline and ceftiofur, respectively, in the canine tear film were too low for any effective antimicrobial effect. Oral doxycycline administration could instead have a positive effect on ulcer healing by inhibiting the matrix metalloproteinases responsible for corneal degradation but randomized and masked clinical trials are necessary to confirm its benefit.…”
Section: Antibiotic Treatment Before Corneal Samplingmentioning
confidence: 99%